PENGARUH JUMLAH PELAMAR CALON MAHASISWA S1 TERAPAN MANAJEMEN BISNIS POLSRI TERHADAP MOTIVASI BELAJAR DENGAN PRESTASI YANG DICAPAINYA - Yusleli Herawati; Hendra Sastrawinata; Iin R (Orasi Bisnis : Jurnal Ilmiah Administrasi Niaga, 2015)
State Polytechnic of Sriwijaya is a vocational education that will enter the business market  needs of the high quality graduates. There is one newly programme which is established in 2014 called S1 Applied of Business Management. This  study accept the applicants for new students with the most applicants prospective students S1 Applied in the State Polytechnic of Sriwijaya with number of 1028 candidates for new students. The students who received in this programme only 48 students. The intense competition is 1:21, this means that the programme study aims to explore the number of applicants prospective students who become students of S1 of Business Management  has a significant influence on learning motivation. The method is carried out by distributing questionnaires to the students by tracing the students learning motivation in participating the learning process. This study also aims to complete the data collection, therefore, the data also collected by interviewing. In that case, the population of this research using “sampel jenuh” technique because of the relatively small number of students of the Applied S1 which amount only 48 students. We analyzed the data with simple regression 12.00 version. The result show that the number of applicants prospective students S1 Applied of Business Management  which has been accepted as a student of Applied S1  have influence the learning motivations by 96.8 percent to  the achievement of learning.